Visualization and the development of software connection technique to enhance the usability of science data - Yu, Eunji; Joo, Wonkyun; Choi, Kiseok (International Journal of Engineering and Technology, 2018)
It would be necessary in the future to provide service on not only national R&D information but also science data, but it would be necessary to effectively provide the meta information of currently owned science data before providing primitive data on science data. In this study, using visualization technique, this study will propose a science data map service model to visualize the information of science data into a transnational science data map, as well as to easily acquire the meta information of desired science data. Also, in order to enhance the usability of acquired information, this study will also suggest a way to immediately use acquired information by interworking with various simulation software. Through the service developed in this study, researchers have been able to acquire science data and usable simulation information without accessing different services.Â